ANALISIS GENDER ATAS AYAT-AYAT REPRODUKSI PEREMPUAN DALAM AL-QUR’AN - Nafisatul Mu'awwanah (Institut Agama Islam Negeri Ponorogo, 2021)
Abstract:In addition to experiencing a heavy reproductive burden, women often receive discriminatory treatment from society because of the reproductive cycle they experience. Discriminatory behavior like this was reflected in preIslamic Arab society, wherein the Alquran came down to carry out a cultural transformation of the patriarchal system at that time. This paper is a critical study of the verses of the Alqur’an about women’s reproduction from a gender perspective. In the study of gender, at least this paper tries to reveal two things: first, how to understand the reproductive verses of women in the Alqur’an; second, what is the form of cultural transformation of the Alquran towards gender discrimination related to the women’s reproductive system. From the results of the study it can be concluded that; first, the Alquran has discussed various women’s issues, including issues related to their reproductive system. There are at least five women reproductive cycles discussed in the Alqur’an, namely regarding menstruation, conception or sex, pregnancy, childbirth, and breastfeeding. Second, when referring to pre-Islamic Arabic culture, the Alqur’an has actually carried out a cultural transformation of a patriarchal system that is very discriminatory against women. The Qur’an emphasizes that men and the environment are involved regarding the responsibilities and risks of the reproductive system experienced by women.Kata Kunci: The verses of the Al qur’an on Women’s Reproduction, Gender Justice, the Reproductive Cycle of Women.Abstrak:Di samping mengalami beban reproduksi yang berat, perempuan kerap mendapatkan perlakuan yang diskriminatif dari masyarakat karena siklus reproduksi yang dialaminya. Prilaku diskriminatif seperti ini tercermin dalam masyarakat Arab pra-Islam, yang selanjutnya Alqur’an turun untuk melakukan transformasi kultural terhadap sistem patriarki ketika itu. Tulisan ini merupakan kajian kritis atas ayat-ayat Alqur’an tentang reproduksi perempuan dalam perspektif gender. Dalam kajian gender, paling tidak tulisan ini berusaha mengungkap tentang dua hal: pertama, bagaimana pemahaman ayat-ayat reproduksi perempuan dalam Alqur’an; kedua, bagaimana bentuk transformasi kultural Alqur’an terhadap diskriminasi gender yang berkaitan dengan sistem reproduksi perempuan. Dari hasil kajian dapat disimpulkan bahwa; pertama, Alqur’an telah membicarakan berbagai persoalan perempuan, termasuk di dalamnya persoalan-persoalan yang berkaitan dengan sistem reproduksi mereka. Setidaknya terdapat lima siklus reproduksi perempuan yang dibicarakan oleh Alqur’an, yaitu berkenaan dengan menstruasi, pembuahan atau seks, kehamilan, melahirkan, dan menyusui. Kedua, ketika merujuk kepada kebudayaan Arab pra-Islam maka sesungguhnya Alqur’an telah melakukan transformasi kultural terhadap sistem patriarki yang sangat diskriminatif terhadap perempuan. Alqur’an menegaskan agar laki-laki dan lingkungan turut terlibat terkait tanggung jawab dan resiko sistem reproduksi yang dialami perempuan.Keywords: Ayat-ayat Reproduksi Perempuan, Keadilan Gender, Siklus Reproduksi Perempuan.